Eco-materials processing and design XIII - Sun, Jing (Materials science forum, 2012)
This work brings together 465 peer-reviewed papers on Advanced Materials and Engineering Technology. It will certainly promote the development of these fields, strengthen international academic cooperation and communication and engender the exchange of research ideas. It provides the reader with a broad overview of the latest advances in the field of advanced materials and engineering technology. Review from Book News Inc.: The current status and trends in creating, processes sing, and using environmentally friendly material are examined in 112 selected and peer-reviewed papers.